A PROFILE OF PRIMARY SCHOOL READER: PROBLEMS AND SOLUTIONS - Krieķis, Andris; Anspoka, Zenta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In order to ensure a targeted development of literacy in a primary school, it is important to recognize needs and realize experience of the little reader. The article aims to analyze the results of a study of literacy levels, reading habits and needs of pupils studying in classes 2 and 3. The study’s methodology is based on psychological theories about the current development of children of the youngest school age, on necessity theories, linguadidactic theories and educational observation, as well as on teacher polls. The data analyzed in the study was collected from April 2017 to January 2018. The study involved 819 pupils studying in classes 2 and 3. The results of the study have been processed using quantitative (arithmetic mean, frequency distribution) and qualitative (meaning content analysis) methods. They have contributed to the development of the profile of the Latvian starting school reader, and have exposed the difficulties encountered by students while learning and using literacy, as well as the reading habits of pupils and the main causes to draw attention to in the primary education process, in order to improve the level of literacy and gradually turn in a proficient reader.